New Evidence on the Effects of the Shortened School Duration in the German States - An Evaluation of Post-School Education Decisions - Tobias Meyer; Stephan Thomsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Most German states have reformed university preparatory schooling by reducing duration from 13 to 12 years with unchanged graduation requirements. The reform was implemented in the states during the last decade in several consecutive years. In this paper, we use nationwide data on high school graduates to evaluate the reform effects on post-school education decisions. The results show that the reform has reduced (or at least delayed) university enrollment of females, but increased the probability of starting vocational education. A similar trend is found for male students, but only in the first year after school graduation. In addition, students are slightly more likely to do voluntary service or spend a year abroad after high school graduation.
Keywords: I21; J18; C21; 330